1994
DOI: 10.1002/chin.199401231
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Unexpectedly Stable Sulfenic Acid: 4,6‐Dimethoxy‐1,3,5‐triazine‐2‐ sulfenic Acid; Synthesis, Properties, Molecular and Crystal Structure.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In particular, we have no knowledge of the spectral features of sulfenic acid or sulfenate in this region of the UV spectrum, but studies with several small molecules stabilizing sulfenic acids have previously reported absorbance features in this region of the spectrum. 43,44 Furthermore, with the significant conformational changes associated with disulfide bond formation in AhpC, the environment of various residues is shifted and could contribute to the observed absorbance changes at 240 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, we have no knowledge of the spectral features of sulfenic acid or sulfenate in this region of the UV spectrum, but studies with several small molecules stabilizing sulfenic acids have previously reported absorbance features in this region of the spectrum. 43,44 Furthermore, with the significant conformational changes associated with disulfide bond formation in AhpC, the environment of various residues is shifted and could contribute to the observed absorbance changes at 240 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The oxidation of 4,6-dimethoxy-1,3,5-triazine-2(1H)-thione (38) with 2-benzenesulfonyl-3- p -nitrophenyloxaziridine in THF solution gave 4,6-dimethoxy-1,3,5-triazine-2-sulfenic acid (39) as a stable crystalline solid (Scheme 4, equation 5). According to their 13 C NMR and X-ray analysis, 39 adopts the sulfenyl structure in condensed phase but in the crystal, the molecules form dimers linked by two strong intermolecular hydrogen bonds [38]. In another interesting study on the synthesis of unnaturally configured cephalo-sporins from 6-phthalimidopenicillanates, Baldwin et al isolated an unusually stable azitidinone sulfenic acid (41) (Scheme 4, equation 6).…”
Section: The Chemistry Of Sulfenic Acidmentioning
confidence: 99%
“…In some cases, proteins containing sulfenic acids may exhibit a low extinction absorbance band (ε max of ∼320 to 370 nm) due to the presence of the deprotonated sulfenate species (Poole and Ellis, 2002), as has been observed previously in small molecules (Tripolt et al, 1993). In these cases, lowering of the pH to protonate this group will result in the disappearance of this absorbance band.…”
Section: Determination Of the Protein Sulfenic Acid Dissociation Consmentioning
confidence: 62%